Understanding Scholarly Presuppositions: A Crucial Tool for Research? - Helm, Paul 1940- (1993)
It is argued that all scholarly enquiry unavoidably rests on either tacitly or explicitly accepted presuppositions. Such presuppositions control enquiry with varying degrees of strength, functioning either as axioms or methodological assumptions. In the interests of objectivity the Christian scholar has the duty to test his own presuppositions by reference to the primary documents of his faith, and by reflecting upon the different presuppositions adopted by other scholars. The quest for scholarly objectivity must not be confused with neutrality.
Keywords: Objectivity; Presuppositions; scholarly methodology; Philosophical Theology